2018
DOI: 10.3389/fmicb.2018.02119
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Rhizobacterium Pseudomonas sp. 23S Induces Systemic Resistance in Tomato (Solanum lycopersicum L.) Against Bacterial Canker Clavibacter michiganensis subsp. michiganensis

Abstract: Tomato bacterial canker disease, caused by Clavibacter michiganensis subsp. michiganensis (Cmm) is a destructive disease and has been a serious concern for tomato industries worldwide. Previously, a rhizosphere isolated strain of Pseudomonas sp. 23S showed antagonistic activity toward Cmm in vitro. This Pseudomonas sp. 23S was characterized to explore the potential of this bacterium for its use in agriculture. Pseudomonas sp. 23S possesses ability to solubilize inorganic phosphorus, and to produce siderophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 80 publications
1
34
0
2
Order By: Relevance
“…The use of plant growth promoting bacteria (PGPB) is a promising alternative with low environmental impact to increase the efficiency of use of mineral fertilizers, including phosphate, providing high cost-effective yields (Spolaor et al, 2016). The PGPB promote plant growth due to various mechanisms such as biosynthesis of phytohormones and secondary metabolites (Duca et al, 2014;Tahir et al, 2017), biological nitrogen fixation (Li et al, 2017), induction of resistance to biotic stresses (phytopathogen biocontrol) and abiotic stresses (drought and salinity) (Yan et al, 2016;Takishita et al, 2018) production of siderophores metal accumulator (Ali et al, 2014) and soil nutrient solubilization such as phosphorus and potassium (Gupta et al, 2015;Shen et al, 2016;Patel and Archana, 2017). Bacteria with combination of these mechanisms, promote and increase the productivity of several crops (Kumar et al, 2014;Smith et al, 2015;Galindo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of plant growth promoting bacteria (PGPB) is a promising alternative with low environmental impact to increase the efficiency of use of mineral fertilizers, including phosphate, providing high cost-effective yields (Spolaor et al, 2016). The PGPB promote plant growth due to various mechanisms such as biosynthesis of phytohormones and secondary metabolites (Duca et al, 2014;Tahir et al, 2017), biological nitrogen fixation (Li et al, 2017), induction of resistance to biotic stresses (phytopathogen biocontrol) and abiotic stresses (drought and salinity) (Yan et al, 2016;Takishita et al, 2018) production of siderophores metal accumulator (Ali et al, 2014) and soil nutrient solubilization such as phosphorus and potassium (Gupta et al, 2015;Shen et al, 2016;Patel and Archana, 2017). Bacteria with combination of these mechanisms, promote and increase the productivity of several crops (Kumar et al, 2014;Smith et al, 2015;Galindo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth-promoting rhizobacteria (PGPR) may affect plant growth, development, and disease suppression by one or more direct or indirect mechanisms. Bacterial genera such as Bacillus and Pseudomonas have been extensively studied and utilized as biocontrol agents, biofertilizers, and also have been shown to trigger induced systemic resistance (ISR) [18][19][20][21][22][23][24]. In this review, we discuss the importance, functions, and effects of root-derived organic molecules secreted in the rhizosphere and their interactions with plant growth-promoting rhizobacteria (PGPR) for enhancing plant growth and biological control of plant pathogens.…”
mentioning
confidence: 99%
“…Work in our laboratory has shown that the B. thuringiensis strain producing thuricin 17 also produces the very effective insecticide beta-exotoxin. In addition, we have recently isolated a pair of compounds, produced by a plant growth-promoting rhizobacteria (PGPR), that are effective against a tomato pathogen (Takishita et al, 2018). These are examples of compounds produced by the phytomicrobiome that can be commercialized to improve crop productivity.…”
Section: Evolved Benefits Of Plant-microbe Interactionsmentioning
confidence: 99%